2022
DOI: 10.1002/anie.202214729
|View full text |Cite
|
Sign up to set email alerts
|

Single Atom Ring Contraction of Peptide Macrocycles Using Cornforth Rearrangement

Abstract: Site-selective transformations of densely functionalized scaffolds have been a topic of intense interest in chemical synthesis. Herein we have repurposed the rarely used Cornforth rearrangement as a tool to effect a single-atom ring contraction in cyclic peptide backbones. Investigations into the kinetics of the rearrangement were carried out to understand the impact of electronic factors, ring size, and linker type on the reaction efficiency. Conformational analysis was undertaken and showed how subtle differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Nevertheless, several macrocycles exhibit decent membrane permeability due to the so-called chameleonic behavior. This comprises exposing polar atoms in an open state in polar solvents and minimizing polar surfaces in a closed state in apolar environments, such as a membrane. The latter can be achieved by shielding of the polar surface with bulky hydrophobic fragments or formation of intramolecular hydrogen bonds (IMHBs); however, the chemical nature of chameleonicity is under debate and its quantitative measurements for cell permeability predictions remain partially unclear. , More studies on conformational preferences in different environments are needed to fully understand the mechanism of chameleonic membrane passing and the solvation of macrocycles in polar and apolar environments. , Due to their unconventional conformational changes, such as peptidic bond inversions, , dynamic patterns of the dense IMHBs, , and restrained ring deformations, short classical molecular dynamics (MD) simulations hardly capture different conformational states. Exhaustive sampling of the conformational spaces remains challenging. , …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several macrocycles exhibit decent membrane permeability due to the so-called chameleonic behavior. This comprises exposing polar atoms in an open state in polar solvents and minimizing polar surfaces in a closed state in apolar environments, such as a membrane. The latter can be achieved by shielding of the polar surface with bulky hydrophobic fragments or formation of intramolecular hydrogen bonds (IMHBs); however, the chemical nature of chameleonicity is under debate and its quantitative measurements for cell permeability predictions remain partially unclear. , More studies on conformational preferences in different environments are needed to fully understand the mechanism of chameleonic membrane passing and the solvation of macrocycles in polar and apolar environments. , Due to their unconventional conformational changes, such as peptidic bond inversions, , dynamic patterns of the dense IMHBs, , and restrained ring deformations, short classical molecular dynamics (MD) simulations hardly capture different conformational states. Exhaustive sampling of the conformational spaces remains challenging. , …”
Section: Introductionmentioning
confidence: 99%
“…Our lab has also previously utilized nitrilium ion intermediates in peptide macrocycles to effect an efficient macrocyclic ring-contraction strategy. 9 Given our group's emerging interest in the synthesis and the structural features of heterobiaryl and bis(heteroaryl) containing peptides, we were keen to develop a new macrocyclization strategy that would allow for facile synthesis of heterobiaryl-containing peptide macrocycles without the reliance on transition-metal catalysis or the need to prepare building blocks that are suitably protected for Fmoc Solid-Phase Peptide Synthesis (SPPS). [9][10][11][12][13] The isocyanide reagent Pinc has proven to be a powerful reagent for macrocyclization.…”
Section: Introductionmentioning
confidence: 99%
“…9 Given our group's emerging interest in the synthesis and the structural features of heterobiaryl and bis(heteroaryl) containing peptides, we were keen to develop a new macrocyclization strategy that would allow for facile synthesis of heterobiaryl-containing peptide macrocycles without the reliance on transition-metal catalysis or the need to prepare building blocks that are suitably protected for Fmoc Solid-Phase Peptide Synthesis (SPPS). [9][10][11][12][13] The isocyanide reagent Pinc has proven to be a powerful reagent for macrocyclization. 7,8,11 Given these advances, we were motivated to utilize Pinc and closely related ethyl 2-isocyano-2-(triphenyl-l 5 -phosphanylidene) acetate (Pinc2) to generate a series of oxadiazole and oxazole heterobiaryl linkages as part of a macrocyclization protocol enabled by the nucleophilic trapping of nitrilium intermediates (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Given our group's interest in the synthesis and the structural features of heterobiaryl and bis(heteroaryl) containing peptides, we were keen to develop a new macrocyclization strategy that would allow for facile synthesis of heterobiaryl containing peptide macrocycles without the reliance on transition-metal catalysis or the need to prepare building blocks that are suitably protected for Fmoc SPPS. [7][8][9][10][11][12][13] (N-isocyanoimino)triphenylphosphorane (1), commonly known as Pinc, has proven to be a powerful reagent for macrocyclization. 13 We previously showed that oxadiazole-grafted peptide macrocycles prepared from reagent Pinc possess predictable secondary structure.…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has also previously utilized nitrilium ions intermediates in peptide macrocycles to effect an efficient macrocyclic ring contraction strategy. 8 Given these advances, we were motivated to utilize Pinc and its close relative 2 to generate a series of oxadiazole-and oxazoleheterobiaryl linkages as part of a macrocyclization protocol enabled by the nucleophilic trapping of nitrilium intermediates.…”
Section: Introductionmentioning
confidence: 99%